Modelling high-frequency volatility and liquidity using multiplicative error models - Nikolaus Hautsch; Vahidin Jeleskovic (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
In this paper, we study the dynamic interdependencies between high-frequency volatility, liquidity demand as well as trading costs in an electronic limit order book market. Using data from the Australian Stock Exchange we model 1-min squared mid-quote returns, average trade sizes, number of trades and average (excess) trading costs per time interval in terms of a four-dimensional multiplicative error model. The latter is augmented to account also for zero observations. We find evidence for significant contemporaneous relationships and dynamic interdependencies between the individual variables. Liquidity is causal for future volatility but not vice versa. Furthermore, trade sizes are negatively driven by past trading intensities and trading costs. Finally, excess trading costs mainly depend on their own history.
Keywords: C13; C32; C52; 330; Multiplicative error models; volatility; liquidity; high-frequency data; Börsenkurs; Volatilität; Börsenumsatz; Marktliquidität; Fehlerkorrekturmodell; Aktienmarkt; Zeitreihenanalyse; Schätzung; Australien